Identification and comparison of pyrolysis products of different biomasses from agro-industrial using TGA-FTIR and Py-GC/MS - Marco Vinicio Rosero Espín; Morayma Angelica Muñoz Borja; Ricardo Andrés Narvaez Cueva; Boris German Insuasti; Sebastian Espinoza; Angela Nuria García Cortés; Antonio Marcilla Gomis (Center of Biomass & Renewable Energy (CBIORE), 2026)
The valorization of agro-industrial residues is crucial for the circular bioeconomy. This study elucidates the thermal decomposition mechanisms and volatile product distribution of four distinct Ecuadorian biomasses: balsa wood (Bl), sugarcane bagasse (Bg), cocoa husks (Cc), and coffee husks (Cf), TGA kinetics. TGA and DTG profiles showed the characteristic multistage degradation of lignocellulosic materials, with maximum mass-loss rates occurring between 320 and 360 °C depending on the biomass. Bl and Bg, which contained the highest cellulose fractions (33–35%), exhibited sharp DTG peaks and higher decomposition temperatures. In contrast, Cc and Cf, both lignin-rich residues (up to 42–47%)—displayed broader degradation profiles, delayed devolatilization, and higher char yields (>26%). Kinetic evaluation confirmed these trends, with cellulose-rich samples showing higher activation energies than lignin-dominated husks. The in-situ FTIR monitoring revealed clear compositional differences in evolved gases: Bl and Bg generated higher proportions of CO and carbonyl-containing volatiles, whereas Cc and Cf produced more CO₂ and phenolic signals associated with lignin fragmentation. Py-GC/MS supported these observations, identifying dominant aldehydes and alcohols in Bl and Bg, while Cc and Cf produced elevated levels of phenols, guaiacols, and nitrogenous aromatics. Overall, the integration of TGA–FTIR and Py-GC/MS allowed establishing direct correlations between lignocellulosic composition, kinetic parameters, and volatile speciation. Unlike previous studies that report either kinetic parameters or volatile fingerprints separately, this work establishes direct kinetic–molecular correlations between activation energy domains and dominant volatile families for Ecuadorian biomasses. The results indicate that balsa wood is a promising feedstock for generating oxygenated chemical intermediates, whereas coffee husk shows strong potential for biochar-oriented processes due to its high lignin content and char yield. These findings expand the thermochemical characterization of Ecuadorian agro-industrial residues and support their selective valorization through pyrolysis.